Analisis Peran Human Resources Department Dalam Meningkatkan Employer Branding Untuk Menarik Kandidat Berkualitas - I Putu Bagus Purnama Putra; I.A. Oka Martini (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Employer branding strategy remains a challenge for many companies. Companies face various obstacles in recruiting candidates who meet the required qualifications. This study aims to analyze the role of human resources department management in improving employer branding to attract quality candidates at PT. Khrisna Multi Lintas Cemerlang. This study uses a descriptive qualitative approach in the form of descriptive information from interviews and observations. In qualitative research, the quality of research is highly dependent on the quality and completeness of the resulting data. The data is then analyzed through steps such as data reduction, data presentation, and drawing conclusions. In checking the data, the researcher uses a data validity checking technique, namely triangulation. The results of this study indicate that the role of HRD in strengthening employer branding at PT. Khrisna Multi Lintas Cemerlang includes strategy formulation, communication of values ​​and culture, social media management, cross-division collaboration, and evaluation of branding effectiveness. Therefore, HRD not only functions as a human resource manager, but also as a strategic actor that contributes to the company's reputation and long-term business success. The strategies implemented by the Human Resources Department to strengthen employer branding to attract qualified candidates include: formulating strategies aligned with the company's vision and mission, consistently communicating company values ​​and culture, utilizing social media as a branding channel, cross-divisional collaboration for strategy integration, and periodically evaluating branding effectiveness.